DNA damage repair mutations in pancreatic cancer– prognostic or predictive? - Hu, Ya-Fei; Hu, Hai-Jie; Kung, Heng-Chung; Lv, Tian-Run; Yu, Jun; Li, Fu-Yu (Frontiers in Oncology, 2023)
The efficacy of platinum-based chemotherapy (PtCh) for pancreatic cancer (PC) patients with DNA damage repair gene mutations (DDRm) compared to those without DDRm remains uncertain. After a thorough database searching in PubMed, Embase, and Web of Science, a total of 19 studies that met all the inclusion criteria were identified. The primary outcomes were overall survival (OS) and progression-free survival (PFS) for PC patients with DDRm versus those without DDRm after PtCh. Patients with advanced-stage PC who have DDRm tend to have longer OS compared to patients without DDRm, regardless of their exposure to PtCh (HR=0.63; I 2 =66%). Further analyses indicated the effectiveness of PtCh for OS was modified by DDRm (HR=0.48; I2 =59%). After the first line PtCh (1L-PtCh), the PFS of advanced-stage PC with DDRm was also significantly improved (HR=0.41; I2 =0%). For patients with resected PC, regardless of their exposure to PtCh, the OS for patients with DDRm was comparable to those without DDRm (HR=0.82; I2 =71%). Specifically, for patients with resected PC harboring DDRm who received PtCh (HR=0.85; I2 =65%) and for those after non-PtCh (HR=0.87; I2 =0%), the presence of DDRm did not show a significant association with longer OS. 1L-PtCh treatment is correlated with favorable survival for advanced-stage PC patients with DDRm. For resected-stage PC harboring DDRm, adjuvant PtCh had limited effectiveness. The prognostic value of DDRm needs to be further verified by prospective randomized controlled trials.